2016
DOI: 10.1371/journal.pone.0152130
|View full text |Cite
|
Sign up to set email alerts
|

Potential Sources and Transmission of Salmonella and Antimicrobial Resistance in Kampala, Uganda

Abstract: In sub‒Saharan Africa, non‒typhoidal Salmonellae (NTS) cause invasive disease particularly in children and HIV infected adults, but the disease epidemiology is poorly understood. Between 2012 and 2013, we investigated NTS sources and transmission in Kampala. We detected Salmonella in 60% of the influent and 60% of the effluent samples from a wastewater treatment plant and 53.3% of the influent and 10% of the effluent samples from waste stabilization ponds that serve the human population; 40.9% of flush‒water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 46 publications
2
57
1
Order By: Relevance
“…As reported in Burkina Faso and in the others parts of the world, Salmonella from fresh vegetables (carrots, radish, lettuce and parsley) play important role in foodborne disease (Afema et al, 2016;Islam et al, 2004;Koffi-Nevry et al, 2012;Traoré et al, 2015). We speculate that lettuce as well as fresh vegetables consumption without food safety measurement is a high risk of foodborne disease such as Salmonella different serotypes isolated but further research is needed to explore more this hypothesis by using modern techniques.…”
Section: Discussionmentioning
confidence: 63%
“…As reported in Burkina Faso and in the others parts of the world, Salmonella from fresh vegetables (carrots, radish, lettuce and parsley) play important role in foodborne disease (Afema et al, 2016;Islam et al, 2004;Koffi-Nevry et al, 2012;Traoré et al, 2015). We speculate that lettuce as well as fresh vegetables consumption without food safety measurement is a high risk of foodborne disease such as Salmonella different serotypes isolated but further research is needed to explore more this hypothesis by using modern techniques.…”
Section: Discussionmentioning
confidence: 63%
“…Salmonella serovars are often isolated in asymptomatic cattle, sheep, pigs, and non‐domestic ruminants and suids (Afema et al, ; Cummings et al, ; Eguale et al, ; Love et al, ; Zishiri, Mkhize, & Mukaratirwa, ). The magnitude and duration of colonization and shedding of Salmonella in animals vary along the different stages of infection or carriage, and not all infected animals shed Salmonella in faeces continuously (Donoghue, Farnell, Cole, & Donoghue, ).…”
Section: Salmonella Colonization and Shedding In Ruminants And Suidsmentioning
confidence: 99%
“…Campylobacter and Salmonella are recurrently isolated from soil, water bodies, animal houses and effluents (Afema et al, ; Lyimo et al, ; Mhongole, Mdegela, Kusiluka, Forslund, & Dalsgaard, ; O'Mahony, Buckley, Bolton, Whyte, & Fanning, ). Free‐range or extensive systems of animal husbandry mostly practiced in rural resource‐poor settings, poor slurry management on animal farms and in slaughterhouses result in environmental bacterial contamination (Figure ; Afema et al, ). Also, Campylobacter and Salmonella spp.…”
Section: Public Health Risks Associated With Animals Colonized and Shmentioning
confidence: 99%
“…A study performed in Uganda reported S. Newport, S. Guildford, S. Coleypark, S. Damman as frequent pig serotypes (26), previously described in humans. Osman et al (27), evidenced S. Haifa in duck embryos, this serotype has also been isolated from bovine feces (28), and humans (26), suggesting adaptation to different animal species. Additionally, S. London an unusual serotype was also identified.…”
Section: Resultsmentioning
confidence: 95%